Revealing the role of the human blood plasma proteome in obesity using genetic drivers - Zaghlool, Shaza B.; Sharma, Sapna; Molnar, Megan; Matías-García, Pamela R.; Elhadad, Mohamed A.; Waldenberger, Melanie; Peters, Annette; Rathmann, Wolfgang; Graumann, Johannes; Gieger, Christian; Grallert, Harald; Suhre, Karsten (Nature communications, 2021)
Blood circulating proteins are confounded readouts of the biological processes that occur in different tissues and organs. Many proteins have been linked to complex disorders and are also under substantial genetic control. Here, we investigate the associations between over 1000 blood circulating proteins and body mass index (BMI) in three studies including over 4600 participants. We show that BMI is associated with widespread changes in the plasma proteome. We observe 152 replicated protein associations with BMI. 24 proteins also associate with a genome-wide polygenic score (GPS) for BMI. These proteins are involved in lipid metabolism and inflammatory pathways impacting clinically relevant pathways of adiposity. Mendelian randomization suggests a bi-directional causal relationship of BMI with LEPR/LEP, IGFBP1, and WFIKKN2, a protein-to-BMI relationship for AGER, DPT, and CTSA, and a BMI-to-protein relationship for another 21 proteins. Combined with animal model and tissue-specific gene expression data, our findings suggest potential therapeutic targets further elucidating the role of these proteins in obesity associated pathologies. Blood circulating proteins reflect biological processes, thus providing insight into complex traits. Here the authors study the relationship between 1000 plasma proteins and body mass index (BMI), highlighting widespread proteome changes and causal relationships between BMI and specific proteins.